Reduksi Volume Dan Pengarangan Kotoran Sapi Dengan Metode Pirolisis - Wijayanti, Widya; Sasongko, Mega Nur (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2012)
The study was conducted to determine the change of mass, the shrinking volume and the heating value of char of cow dung induced by slow pyrolysis. The char produced by pyrolysis can be used as an alternative solid fuels. Besides, it can be a biochar as a mixture of biomaterial having a high-value materials. It due to the char has a high content of Carbon. In this experiment, the heating value of char was examined by using bomb calorimeter. The temperature pyrolysis was varied from 100°C to 500°C. Before the pyrolysis process, the feedstock was pulverized to a particle size of about 0.7 mm, and then it dried in the oven to have a moisture content up to 4%. The pyrolisis was conducted at varied temperatures and different heating rates from 0.13°C /sec to 0.29°C /sec.The results showed that the reduction of the cow dung volume performed significantly by the way of slow pyrolysis. The most reduced volume of cow dung occured very significant at the highest pyrolysis temperature, reaching 60% at 500°C. On the other hand, the heating rate variation did not influence in yield reduction, but it has an effect on the result of heating value of char. The results also indicated that the optimal of heating rate occured at 0.13°C/sec to 0.16°C/sec. In the visualization of the solid yield pyrolysis products, as higher pyrolysis temperature, as darker color of the char. It was shown the Carbon content in the char.Keywords: cow dung, pyrolysis temperature, heating rate, heating value, char